Kanoniczne przesłanki formalno-porządkowe i ceremonia zawarcia małżeństwa przez pełnomocnika w Kościele łacińskim w Polsce - Świto, Lucjan; Tomkiewicz, Małgorzata (Ius Matrimoniale, 2018)
The contraction of a marriage by proxy is a tradition deeply embedded in the Church history and, although it is rare in practice, it is still present in the canon law. The contraction of a marriage while one of the nuptrients is absent is obviously far from a typical situation and not well recognized in the church practice and canon doctrine, which raises some doubts. The first question that appears is whether, due to the specific nature of matrimonium per procura, are the canonical requirements regarding the activities directly preceding the contraction of marriage still valid? Are all the regulations applied when both nuptrients are physically present also required of the nuptrients who cannot be present at the marriage contraction? What are the consequences of the potential breaches in this matter? Is the ceremony itself of the marriage contraction by proxy in any way different than the ‘classic’ ceremony, and if so – what are these differences? This article is an attempt to answer these questions, presenting the relevant regulations of the canon law concerning the subject matter.